Transforming U.S. army supply chains : strategies for management innovation - Parlier, Greg H. (New York : Business Expert Press, 2011)
This text offers a practical approach for understanding the U.S. Army's extremely complex global logistics system, widely acknowledged as one of the largest in the world. The focus is on inventory management policy where prescriptions are illuminated through the prism of an enterprise supply chain analysis. -- Abstracts.
Includes bibliographical references and index.
Keywords: United States. -- Army -- Supplies and stores -- Inventory control; Logistics